Potential of Ceria-Based Catalysts for the Oxidation of Landfill Leachate by Heterogeneous Fenton Process - E. Aneggi; V. Cabbai; A. Trovarelli; D. Goi (International Journal of Photoenergy)
In this study, ceria and ceria-zirconia solid solutions were tested as catalyst for the treatment of landfill leachate with a Fenton-like process. The catalysts considered in this work were pure ceria and ceria-zirconia solid solutions as well as iron-doped samples. All the catalysts were extensively characterized and applied in batch Fenton-like reactions by a close batch system, the COD (chemical oxygen demand) and TOC (total organic carbon) parameters were carried out before and after the treatments in order to assay oxidative abatement. Results show a measurable improvement of the TOC and COD abatement using ceria-based catalysts in Fenton-like process and the best result was achieved for iron-doped ceria-zirconia solid solution. Our outcomes point out that heterogeneous Fenton technique could be effectively used for the treatment of landfill leachate and it is worth to be the object of further investigations.